The Morphometric Status of the Macula in Children with Pseudophakia after Surgical Treatment of Congenital Cataracts - L. A. Katargina; T. B. Kruglova; N. S. Egiyan; D. I. Ryabtsev; O. B. Trifonova (Российский офтальмологический журнал, 2018)
The paper presents the results of a comprehensive ophthalmic examination which includes, along with traditional methods, optical coherence tomography (taken by Spectralis HRA+OCT, Heidelberg Engineering) of 33 children (50 eyes) aged 1 to 7 years with pseudophakia after extraction of bilateral congenital cataracts (CC). Extraction of CC with IOL implantation was administered to children at the age from 4 to 36 months. The optical power of the IOL was determined by the standard formula SRKII. OCT was used to evaluate the following parameters: the minimum thickness of the retina in the fovea, the maximum thickness of the retina in parafovea, retinal thickness at 3.0 mm from foveola, the width (diameter) of the fovea, and the thickness of the choroid in the subfoveal area. The morphometric examinations of the status of the central fundus area in children with pseudophakia after CC revealed the smoothing of the foveolar depression, which is directly dependent on the child’s age at the time of surgery. The trends to fovea diameter reduction and choroid thinning revealed in the cases of surgeries performed at later stages testify to the need of further comprehensive research into the mechanisms underlying impaired formation of the macular area which could help identify the criteria for the prognosis of visual functions in children with CC // Russian Ophthalmological Journal, 2016; 1: 27-31.